Cece loves science : push and pull - Derting, Kimberly; Johannes, Shelli R. (Greenwillow Books, an Imprint of HarperCollins Publishers, 2020)
Cece and her friend Isaac conduct an experiment to see if Cece's dog, Einstein, will eat vegetables. Includes glossary and activities using the forces of push and pull.